Qualitative study of Ebola screening at ports of entry to the UK. Issue 3 (27th June 2018) - Kesten, Joanna May; Audrey, Suzanne; Holding, Maya; Coope, Caroline; Young, Nick; Brown, Colin S; Harries, Jenny; Hickman, Matthew; Oliver, Isabel
Abstract : Introduction: In response to the 2013–2016 West African outbreak of the Ebola virus disease (EVD), Public Health England introduced enhanced screening at major UK ports of entry. Our aim was to explore screeners' and screened travellers' perceptions of screening as part of an evaluation of the screening programme. Methods: We undertook qualitative focus groups and semistructured interviews with screeners and travellers who had returned from affected countries before and after the introduction of screening in England. The study was conducted in two airports: one international rail terminal and one military airport. Research topic guides explored perceptions of the purpose and implementation of the process, potential improvements and reactions to screening. The data were analysed using the framework method. Results: Twenty-four screeners participated in 4 focus groups (one for each port of entry) and 23 travellers participated in interviews. Three themes are presented: 'Context', 'Screeners' experience of the programme' and 'Screening purpose and experiences'. The programme was implemented rapidly, refined over time and adapted to individual ports. Screeners reported diverse experiences of screening including negative impacts on their normal roles, difficult interactions with passengers and pressure to identify positive EVD cases. Screening was considered unlikely to identify individuals with symptoms of EVD, and some participants suggested it was driven by political concerns rather than empirical evidence. The screening process was valued for its provision of information and reassurance. Conclusion: This qualitative study found that the UK EVD screening process was perceived to be acceptable to assess individual risk and provide information and advice to travellers. Future programmes should have clear objectives and streamlined processes to minimise disruption, tailored to the nature of the threat and developed with the needs of humanitarian workers as well as general travellers in mind.